Contributions of Cunha Rivara (1809–1879) to the development of Konkani - Fernandes, Gonçalo (2019)
Joaquim Heliodoro da Cunha Rivara (1809–1879) was a Portuguese physician, professor of philosophy, politician, librarian and secretary of the governor-general of India (1855–1870). During his job in Goa, he gave a strong impulse to the development of Konkani, a provincial language of Goa. On 28 November 1857, he was appointed by the governor-general to lead a commission established to coordinate, prepare and print Portuguese-Konkani and Konkani-Portuguese dictionaries and other “monuments” of the same language. In addition to many books with primary documentation of the history of Portuguese in India, he published a Historical Essay on Konkani Language that he wrote himself; a grammar by Thomas Stephens, S.J. (1549–1619); an anonymous grammar, possibly written in the 17th century by a Franciscan or Jesuit living in Thane, on Salsette Island; and a grammar and a dictionary written probably by the Vicar Apostolic of Verapoly from 1831 to 1844, Francesco Saverio di Sant’Anna, O.C.D. (1771–1844), which circulated as manuscripts. His intense editorial activity in the defense and the dignity of Konkani, against the “despreso da lingua materna” [the contempt of the native language] (Rivara 1857b: CXIII) by Goans, allows us to consider Cunha Rivara the pioneer of the Renaissance of Konkani studies in the 19th century. Despite the fact that he did not know Konkani, Cunha Rivara paved the way for the 20th century Konkanists scholars who were inspired by his publications, such as Gerson da Cunha (1844–1900), Sebastião Dalgado (1855–1922), Shennoi Goembab (1877–1946), Mariano Saldanha (1878–1975) and Joaquim António Fernandes (1889–1975). He also had a substantial impact on the overall development of the study of Konkani.